Improving Oral Health Literacy in the Digital Age: Recommendations for a Collaboration Between the Dental Profession and Voice-Activated Virtual Assistants - Bailey M Hollihan (Wolters Kluwer Medknow Publications, 2018)
Within the healthcare system, patients continue to take on a larger role in managing their health. However, due to the low prevalence of health literacy among the US adult population, many patients are unable to make appropriate medical decisions. The Internet is further contributing to the problem. Patients are looking to the Internet, which can include extremely complex or inaccurate text, when they have questions about their health more often than speaking with their providers. This presents the risk for patients to become confused, misled, or even believe false information about their health. In order for patients to manage their health successfully, they must develop health literacy. This will be possible through advancements in internet technology that will provide the patients with clear, credible health information.